Experimental investigation of metallic partial-flow particulate filter on a diesel engine's combustion pressure and particle emission - Mi Zwe Mon Phyo; Phyo Wai; Myat Hsu Thin; Ban-Seok Oh; Watanyoo Phairote; Mek Srilomsak; Chinda Charoenphonphanich; Manop Masomtob; Sompong Srimanosaowapak; Hidenori Kosaka; Preechar Karin (My University, 2023)
The study aims to present the combustion and exhaust behaviors of a 3 L, four-cylinder common rail diesel engine with three different kinds of conventional B7 diesel fuels with and without a platinum diesel oxidation catalyst (DOC) system and non-catalytic partial flow through a diesel particulate filter (P-DPF). Testing is performed under the three different operating conditions, idle to medium engine loading at 1000, 1500, and 2000 engine revolutions per minute with four different engine torques of 84, 112, 140 and 160 Nm. The surface morphology and agglomerate size of particulate matter (PM), single primary particle analysis as well as the fringe length of the carbon crystallite structure were also examined using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive x-ray spectroscopy (EDS) to achieve a better understanding through image processing. The P-DPF system does not have a significant effect on an engine's in-cylinder combustion characteristics and brake thermal efficiency. The diesel engine's particle emissions are reduced by trapping them on the metallic micro-fibers of a P-DPF. CO2, NO, and O2 levels show that the carbonaceous particle emissions on the micro-structure of the P-DPF passively react with NO2 and O2. Consequently, diesel engine particle emissions can be reduced by around 50% using a P-DPF system under the experimental conditions of the current study.
Keywords: Particle (ecology); Diesel exhaust fluid; Vehicle emissions and performance